Pengaruh Edukasi Kesehatan Prakonsepsi Dengan Animasi Terhadap Pengetahuan Catin Tentang Persiapan Kehamilan Sehat - Atikah Sulastri; Megayana Yessy Maretta; Erlyn Hapsari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Background: Anemia, chronic energy deficiency (CED), intrapartum bleeding, andlow birth weight (LBW) are complications that can be experienced by mothers andbabies due to inadequate preparation for pregnancy during the preconception period.Good knowledge about pregnancy preparation will encourage expectant mothers tomake efforts to optimize health during the preconception period, namely the periodbefore pregnancy. The bride and groom candidates are expectant mothers who shouldhave good knowledge about preparing for a healthy pregnancy. Education that utilizes animated media is an effective way to increase the knowledge of the bride and groomcandidates about preparing for a healthy pregnancy. This study aims to determine theeffect of preconceptional health education with animation on the knowledge of brideand groom candidate about healthy preparation for pregnancy. The research wasconducted on 72 bride and groom candidates at the Cihara Health Center, LebakRegency, Banten in May-July 2022.Methode: This type of research was a quantitative design with a pretest posttestdesign with a control group. Data analysis used the Wilcoxon and Mann Whitney tests.The results showed that there was a significant difference in knowledge between thetwo groups with a value of p = 0.000. All respondents (100%) in the experimental grouphad good knowledge after being given education with animation, while in the controlgroup, respondents who had good knowledge after education were 33.3%.Conclusion: The conclusion of this study is that preconceptional health educationwith animation is effective in increasing the knowledge of bride and groom candidateabout preparing for a healthy pregnancy.Keywords: Education, Animation, Bride and Groom Candidate